2023
DOI: 10.3390/en16114359
|View full text |Cite
|
Sign up to set email alerts
|

Aluminosilicate Clay Minerals: Kaolin, Bentonite, and Halloysite as Fuel Additives for Thermal Conversion of Biomass and Waste

Abstract: The current focus on renewable energy sources and the circular economy favors the thermal conversion of low-quality fuels, such as biomass and waste. However, the main limitation of their usability in the power sector is the risk of slagging, fouling, ash deposition, and high-temperature corrosion. These problems may be avoided or significantly mitigated by the application of aluminosilicate clay minerals as fuel additives. In this paper, the three most commonly occurring aluminosilicates are reviewed: kaolin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 123 publications
0
8
0
Order By: Relevance
“…of volatile alkaline elements in the fuel used. Research has shown that blending low-quality fuel with additives can lead to a decrease in the formation of solid particles and other combustion by-products, such as NOx, SO2, and HCl, during the combustion process [23].…”
Section: Fuel Selection Preparation and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…of volatile alkaline elements in the fuel used. Research has shown that blending low-quality fuel with additives can lead to a decrease in the formation of solid particles and other combustion by-products, such as NOx, SO2, and HCl, during the combustion process [23].…”
Section: Fuel Selection Preparation and Analysismentioning
confidence: 99%
“…Using additives and combined fuel aims to change the composition of the raw material and additionally reduce the share of volatile alkaline elements in the fuel used. Research has shown that blending low-quality fuel with additives can lead to a decrease in the formation of solid particles and other combustion by-products, such as NOx, SO 2 , and HCl, during the combustion process [23]. During gasification, dolomite undergoes calcination to yield CaO, which acts to prevent agglomeration by favoring the formation of K 2 CO 3 over K 2 OnSiO 2 [24].…”
Section: Introductionmentioning
confidence: 99%
“…(6) Continuous and intensive research on the pyrolysis process and the possibilities of managing its products enrich the world of science and bring the economy and industry closer to the introduction of pyrolysis for use on an industrial scale. (7) Finding new applications for pyrolysis products. Proposal to use pyrolysis gas and biochar for energy purposes, reducing the consumption of conventional fuels.…”
Section: Strengths Weaknessesmentioning
confidence: 99%
“…Improper management of MSW not only has a negative impact on the environment, but also poses a threat to public health and raises other socio-economic problems. Waste-to-energy (WtE) technologies such as pyrolysis, gasification, incineration and biomethanization [7] can convert MSW into usable energy (electricity and heat) in a safe and environmentally friendly way [8].…”
Section: Introductionmentioning
confidence: 99%
“…Clays encompass a diverse group of natural minerals with layered structures, including montmorillonite, kaolinite, smectite, among others. The unique arrangement of layers provides clays with exceptional properties, such as high surface area, swelling capacity and ion exchange capacity [ 23 , 24 ]. Specifically, bentonite and kaolinite are two types of clays with significant differences in their chemical composition, crystal structure, and physicochemical properties, making them useful in the petroleum and gasification industry for the purposes of ceramic manufacturing and wastewater treatment [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%